PROBLEMATIK IMUNITAS HUKUM ANGGOTA PARLEMEN DITINJAU DARI PRINSIP EQUALITY BEFORE THE LAW - Lolong, Wenly R.J (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2015)
Immunity laws and ownership rights by members of Parliament as State officials intoa huge deal lately. The right of immunity that attaches to the Member of Parliament is becomingattractive to examined in comparison with the existence of the principle of equality before thelawThe focus of this study is to analyze the basic concept of building immunity State officialsespecially ownership rights of immunity of members of Parliament, when faced with thefundamental problems in the country namely the presence of equality before the law in everycitizen. The outline of issues raised, namely whether the juridical foundation of legal immunityfor members of Parliament in Indonesia as a privilege that is owned in the context of hisposition as State officials? The second issue is how does the existence of the principle of legalimmunity for State officials when it examined the position and enforceability before theprinciple of equality before the law? As a conclusion here is that the right of immunity of itsexistence included expressly in the UUD 1945 specially section 20A para 3. The elaboration ofadvanced settings of the existence of the right of immunity members of Parliament in factprovided for in Article 224 of the Act Number 17 of 2014 of the MPR, DPR, DPD, dan DPRD.While the principle of equality before the law as a basic principle in the concept of law and thehuman rights embodied in the Constitution by forming the State in article 27 paragraph (1) ofthe Constitution